Potensi Pakih Sipasan (Blechnum orientale) sebagai Antibakteri Terhadap Staphylococcus aureus dan Methicillin Resistant Staphylococcus aureus - Yossi Rahmadeni; Fuji Astuti Febria; Amri Bakhtiar (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2019)
Staphylococcus aureus is an opportunistic pathogenic bacteria. These bacteria can cause infections of the skin, bones, lungs, heart or systemic infections. Giving antibiotics does not fit the recommendations result in the emergence of resistant strains. Methicillin Resistant Staphylococcus aureus (MRSA) is one of the bacteria beta-lactam antibiotic resistant. Pakih Sipasan (Blechnum orientale) is a low level plants that is widely used Simanau villagers at Solok District in overcoming skin infections. The aims of this research are to determine the phytochemical content of B. orientale and to know antibacterial potential against S. aureus and MRSA. This research was conducted in March-July 2017 at Biota Laboratory of Sumatera and Microbiology Research Laboratory of Biology Department, Andalas University. Research method is experiment. The extracts were prepared with concentrations of 20 mg/ml, 40 mg/ml, 60 mg/ml, 80 mg/ml and 100 mg/ml. The data obtained are analyzed and presented in the form of tables and drawings are presented descriptively. The results showed that the B. orientale contain chemical compounds class of alkaloids, phenols and flavonoids. All treatments have potential as antibacterial to S. aureus and MRSA. The antibacterial activity of the B. orientale against S. aureus is stronger than against MRSA. The average diameter of inhibitory zone formed from concentrations of 20 mg/ml to 100 mg/ml of S. aureus ranged from 13.00 mm - 14.95 mm and to against MRSA between 11.31 mm - 14.48 mm. Key words: Staphylococcus aureus, MRSA, phytocemical test, antibacteria, Blechnum orientale